2008
DOI: 10.1213/ane.0b013e3181607262
|View full text |Cite
|
Sign up to set email alerts
|

Candida Albicans Versus Non-Albicans Intensive Care Unit-Acquired Bloodstream Infections: Differences in Risk Factors and Outcome

Abstract: In the subset of critically ill nonimmunosuppressed patients, candidemia caused by non-albicans species occurred more frequently in those with medical devices or receiving steroids. Candidemia due to non-albicans species was also associated with higher mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
128
6
12

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(159 citation statements)
references
References 41 publications
13
128
6
12
Order By: Relevance
“…albicans was isolated from (69%) of cases and (35%) were NAC. A comparable rate were obtained by Dimopoulos et al [8], where C. albicans was recovered from (64.3%) of candidemia episodes in intensive care unit patients compared to NAC from (35.7%). On the contrary Rajendran etal.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…albicans was isolated from (69%) of cases and (35%) were NAC. A comparable rate were obtained by Dimopoulos et al [8], where C. albicans was recovered from (64.3%) of candidemia episodes in intensive care unit patients compared to NAC from (35.7%). On the contrary Rajendran etal.…”
Section: Discussionsupporting
confidence: 83%
“…However different rates were reported by other studies with rates (10.7%), (9%) and (32%) respectively [8,10].…”
Section: Discussionmentioning
confidence: 53%
“…(1,9,10,23) or by potentially fluconazole-resistant organisms (Candida glabrata and Candida krusei) (16,23,28) but have not taken into consideration in vitro resistance to fluconazole. In these studies, prior fluconazole exposure was an independent risk factor for candidemia caused by non-albicans Candida species (1) or by potentially fluconazole-resistant species (23), whereas other studies did not find this association (16,28).…”
mentioning
confidence: 99%
“…This would call attention to the importance of appropriate antibiotic use in hospitals and of antimicrobial stewardship programs in controlling and preventing unnecessary use of antibiotics [24,25]. Previous studies have identified other risk factors associated with non-albicans Candida, including glucocorticoids use, central venous catheter placement, candiduria, male gender, total parental nutrition and recent history of solid tumors [24][25][26][27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%